PENGARUH KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR PADA PEGAWAI KEMENKUNHAM LAPAS MUARO PADANG - Yusnaena Sisca Andayani (Jurnal Menara Ekonomi : Penelitian dan Kajian Ilmiah Bidang Ekonomi, 2017)
The research was carried out, the Ministry of Justice and Human Rights Unit of theRegional Office Papers Prison Class IIA West Sumatra Jl. Muaro No. 42 Padang. Thephenomenon that is found in these establishments are several employees, who simply dotheir job accordingly not optimal. Based on the above background, the authors areinterested in doing more research on "The Effect of Job Satisfaction Against OCB(Organizational Citizenship Behavior) In the ministry of law and human rightsPrison Employees Muaro Padang". The purpose of this study was to determine the effectof job satisfaction on OCB organizational citizenship behavior (OCB) to the employees ofthe prison the ministry of law and human rights Muaro Padang. From the dataprocessing can be seen that the calculated value of t 0,000. This means that thesignificance of less than 0.05. Then satisfaction significantly influence OrganizationalCitizenship Behavior.Keywords: job satisfaction and organizational citizenship behavior